THE TED TALK APPROACH: EFL STUDENT PERCEPTIONS OF ITS IMPACT ON LISTENING COMPREHENSION - Trisnawati, Ika Kana; Sarair, Sarair; Nafaisha, Adilla; Netta, Ayuna; Qamariah, Hijjatul (Jurnal Ilmiah Didaktika, 2025)
This study examined the effectiveness of TED Talks as a learning tool to enhance listening comprehension among senior English Education majors in Indonesia. The objective was to identify whether TED Talks videos helped enhance the listening proficiency of this particular student group. A mixed-methods research study was employed in order to accomplish the aforementioned objective. Students of the English Education departments in semesters six and eight constituted the target population. A voluntary sample of 30 students was selected for participation. Data were gathered through interviews and questionnaires. Quantitative data from the questionnaire were calculated using IBM SPSS 25, and interview data were examined using thematic analysis. Quantitative data showed mean scores ranging from 2.34 to 3.67, categorized as ‘moderate.’ This indicated the general agreement among respondents that TED Talks videos contributed towards an improvement in listening skills. This represented a favorable perspective on the usefulness of the application; however, the ‘moderate’ categorization signaled a need for a deeper investigation into the practical application and optimization of TED Talks. Further, qualitative interview data provided a richer context, complementing the quantitative findings.